2013
DOI: 10.46429/jaupr.v97i1-2.3042
|View full text |Cite
|
Sign up to set email alerts
|

Breaking Seed Coat Dormancy With Physical and Chemical Methods in Tamarind (Tamarindus Indica L.) Seeds

Abstract: BREAKING SEED COAT DORMANCY WITH PHYSICAL AND CHEMICAL METHODS IN TAMARIND (TAMARINDUS INDICA L.) SEEDS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Ayala-Silva et al, [11], reported that mechanical scarification is an effective method of increasing seed coat permeability in Tamarindus indica seeds. Rusdy et al, [12] investigated how mechanical scarification affected the germination of Leucaena leucocephala seeds and concluded that scarifying seeds by clipping the seed coat around the micropyle at the distal end considerably improved germination.…”
Section: Resultsmentioning
confidence: 99%
“…Ayala-Silva et al, [11], reported that mechanical scarification is an effective method of increasing seed coat permeability in Tamarindus indica seeds. Rusdy et al, [12] investigated how mechanical scarification affected the germination of Leucaena leucocephala seeds and concluded that scarifying seeds by clipping the seed coat around the micropyle at the distal end considerably improved germination.…”
Section: Resultsmentioning
confidence: 99%
“…Tamarindus indica L. (tamarind) is a widely distributed tropical fruit tree found in Africa and Asia (Morton, 1987;El-Siddig et al, 1999;Janick and Paull, 2008;Ayala-Silva et al, 2010. Although its precise origin is unknown, most systematists consider tamarind to be indigenous to the drier grasslands of tropical Africa (Gunasena and Hughes, 2000;Ayala-Silva et al, 2013). However, it has long been naturalized in tropical Asia, the Caribbean, Mexico and Central America.…”
Section: Introductionmentioning
confidence: 99%
“…Tamarind, which originated in India, is the only genus belonging to the family Fabaceae (Leguminosae), and it is popularly known as 'Indian Date' (Morton, 1987). It is primarily valued for its fruits, especially the pulp, which is used for a wide variety of domestic and industrial purposes (Morton, 1987;Parrota, 1990;Janick and Paull, 2008;Ayala-Silva et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations